Comparative Study on the Effect of Ultrasonic Power on the Microstructure and Mechanical Properties of 2195 Aluminum Alloy Ingot - Hu, Yuqi; Jiang, Ripeng; Li, Xiaoqian (Frontiers in Materials, 2022)
High-intensity ultrasound was introduced for the casting of 2195 aluminum–lithium alloy ingots. The shape of the ingots was a cylinder with a length of 650 mm and a radius of 30 mm. In this study, the effects of different ultrasonic powers were applied in the melt. The grain shape, α-Al grain size, the size of the precipitated phase, and the mechanical properties of the ingots were compared. The results showed that when the power of the ultrasonic system was maintained at 1,600 W, an ingot with a more uniformly dispersed precipitation phase and grain refinement structure was formed. It can be concluded that the coarse eutectic structure in the ingot is effectively reduced when the power is around 1,600 W, and the mechanical properties of the ingot reach the best value.